Apparatus for the measurement of the thermodynamic speed of sound of diethylene glycol and triethylene glycol. (July 2022) - Javed, Muhammad Ali; Vater, Sebastian; Baumhögger, Elmar; Windmann, Thorsten; Vrabec, Jadran
Highlights: The speed of sound of diethylene glycol and triethylene glycol is measured in the liquid state with the pulse-echo technique. Double polynomial equations were fitted to the speed of sound data of both glycols. The present data are critically compared with all available experimental literature sources. Abstract: The speed of sound is a thermodynamic equilibrium property which relates pressure to density variations at constant entropy. Because of its thermal and caloric nature, thermodynamic speed of sound data are crucial for the parametrization of highly accurate Helmholtz energy equations of state, which are in great demand. In the present work, the thermodynamic speed of sound of diethylene glycol and triethylene glycol is measured with an apparatus based on the pulse-echo technique. The measurements are performed along five isotherms, covering a temperature range between 300 K and 500 K, while the pressure was varied from 0.1 MPa to 45 MPa. The maximum relative expanded uncertainty of the reported data is 0.11% for both glycols. A double polynomial equation is fitted to the present data with a maximum deviation of 0.2% for diethylene glycol and 0.04% for triethylene glycol. A comprehensive comparison with literature data is carried out, confirming the present data at ambient conditions. However, for high temperature isotherms, deviations are up to 2% for diethylene glycol and up to 3% for triethylene glycol.